Sophie Calle: Follow me - Delvaux, Martine (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2006)
This article addresses the question of sexual identity in Sophie Calle's work, in particular in Des histoires vraies + dix and No Sex Last Night. Through the use of sexual stereotypes and an emphasis placed on desire, the failure of sexual encounters and love relationships, the artist questions the notion of identity, whether sexual or simply biographical.